ARTERIALIZATION OF GREAT SAPHENOUS VEIN IN SITU FOR LIMB SALVATION: OUR CLINICAL EXPERIENCES - V Cvetanovski; A Arsovski; L Brajevikj; A Mitevski; M Cvetanovska; B Kondov; Z Dimitrov (Македонско лекарско друштво = Macedonian Medical Association, 2021)
Introduction. Critical lower limb ischemia in the ab-sence of distal arterial circulation presents an urgent situation, which must be treated immediately if we want to save the foot or limb from amputation. Approximately 14%-20% of patients with critical lower limb ischemia are unsuited for distal arterial reconstruc-tion and face major distal amputation [1]. Arterializa-tion of great saphenous vein is a unique procedure in which the venous bed is used as an alternative conduit for perfusion of peripheral tissues of lower limb. Methods. We present our clinical experience in 6 patients who underwent in situ arterialization of great saphenous vein for treatment of critical below- and above-knee ischemia. Maintaining the great saphenous vein in situ allows the arterialization with one anastomosis without removing the vein of its original bed. All patients were diagnosed with color Doppler ultrasound and with CT angiography. Results. In all 6 patients we managed to safe the limb or foot from amputation in the first 6 months after the procedure. Postoperative color Doppler ultrasound was performed to assess arterial inflow and arterialized flow in the graft, the anastomosis and venous run-off. In all patients with significant intraoperative reverse flow in upper and below the knee part of great saphe-nous vein the procedures were initially successful. Conclusion. Distal revascularization of the limb with critical ischemia, by creating a reverse flow with in situ saphenous vein arterialization must be seriously considered as an attempt for salvage of the foot or below-knee without distal arterial run-off.
Keywords: arterialization of vein; great saphenous vein; critical limb ischemia; end-stage peripheral